Evaluating fladry designs to improve utility as a nonlethal management tool to reduce livestock depredation - Julie K. Young; Elizabeth Miller; Anna Essex (Wildlife Society Bulletin)
ABSTRACT Nonlethal deterrents against carnivores are important components to protecting livestock and conserving carnivore populations. However, the performance of the visual deterrent called fladry, a historical tool used to defend livestock from carnivores, is often hindered by design flaws that eventually reduce its effectiveness. Our purpose was to identify a fladry design that reduces coiling (i.e., wrapping of individual flags tight to the rope from which they hang) and maintains free movement of the deterrent in the wind. We created 6 new designs, replicated designs using 2 materials (nylon and marine vinyl), and compared them with the design most commonly used today—where flags were sewn directly onto the line along which they are strung. We conducted the study during January–February 2014 at the U.S. Department of Agriculture, Wildlife Services, Predator Research Facility in Millville, Utah, USA. Fladry made of marine vinyl and attached via 2 of our 6 designs showed the least amount of coiling, were relatively easy to construct, and did not result in significant additional costs. The 2 designs were shower curtain, where the flags are attached via circular links, and knotted, where a knot is tied in the flag below its point of attachment. We suggest users of nylon fladry modify it to one of these designs and advise new users to consider a heavier (e.g., marine vinyl) material. © 2015 The Wildlife Society.